2001
DOI: 10.1002/ar.1159
|View full text |Cite
|
Sign up to set email alerts
|

The spatiotemporal relationship among schwann cells, axons and postsynaptic acetylcholine receptor regions during muscle reinnervation in aged rats

Abstract: To morphologically define the aging-related features during muscle reinnervation the spatiotemporal relationships among the major components of the neuromuscular junctions (NMJs) were investigated. A total of 64 rats, 30 adults (4 months old) and 34 aged adults (24 months old), were used. Between 1 and 12 weeks after sciatic nerve-crushing injury, cryosections of skeletal muscle were single or double labeled for S100, a marker of Schwann cells (SCs), for protein gene product 9.5, a neuronal marker, and for ␣-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 89 publications
(134 reference statements)
4
52
0
1
Order By: Relevance
“…However, such changes in SCs will have an adverse effect on the maintenance of the remaining NMJ and possible re-innervation. Most studies have examined alterations in SCs after nerve crush or transection [44], whereas very few have examined SCs in ageing muscles [45], [46]. An electron microscopic study of gastrocnemius muscles in mice showed no SC degeneration in young adults (6 months) but degeneration of SCs and their processes in 35% of the NMJs at 27 months [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, such changes in SCs will have an adverse effect on the maintenance of the remaining NMJ and possible re-innervation. Most studies have examined alterations in SCs after nerve crush or transection [44], whereas very few have examined SCs in ageing muscles [45], [46]. An electron microscopic study of gastrocnemius muscles in mice showed no SC degeneration in young adults (6 months) but degeneration of SCs and their processes in 35% of the NMJs at 27 months [45].…”
Section: Discussionmentioning
confidence: 99%
“…Impairment in these cells, such as increased fragmentation, damage, or denervation may contribute to ineffective re-innervation and neuromuscular dysfunction in aging (Verge et al, 1996; Kawabuchi et al, 2001, 2011; Gordon et al, 2009). …”
Section: The Aged Neuromuscular Junctionmentioning
confidence: 99%
“…Enhanced expression of a cell-surface glycoprotein, CD44, in PSCs in an ALS mouse model further suggests a potential role of PSCs in the motor neuron disease (Gorlewicz et al 2009). Impaired PSC sprouting seen in aged muscles may also explain the poor reinnervation after nerve injury during aging (Kawabuchi et al 2001). Besides guiding presynaptic nerve terminals, PSCs are thought to play a role in clustering postsynaptic AChRs by expressing neuronal isoforms of agrin at the frog NMJ (Yang et al 2001).…”
Section: Degeneration and Regenerationmentioning
confidence: 99%